Understanding and fixing WMSDs in herbal medicine workers at Luang Por Poen Hospital, Thailand - Dwi Rosella Komalasari; Umi Budi Rahayu; Suryo Saputra Perdana; Tasa Kasumbung; Pakaratee Chaiyawat (University of Merdeka Malang, 2024)
Work-related Musculoskeletal Disorders (WMSDs) affect millions globally, involving painful conditions of muscles, tendons, ligaments, and nerves due to workplace factors like repetitive tasks and awkward postures. Common ergonomic risks include repetitive tasks, awkward postures, forceful exertions, and prolonged static positions. A program at Luang Por Poen Hospital in Thailand educated workers in the Herbal Medicines division on WMSDs, with management support. The program provided education on WMSDs to workers and management, with strong support from company leadership. Workers were instructed to perform muscle stretching exercises before, during, and after work, and to continue these exercises at home. Over a month, supervisors observed workers' stretching routines. The Nordic Body Map Index (NBMI) was used to assess pain; workers reported pain in various body regions. Severe neck pain decreased from six workers to one, and severe back pain from three workers to none. However, severe shoulder pain remained unchanged. No workers reported severe pain in the arm, back, buttock, wrist, calf muscle, or ankle after the program. In conclusion, incorporating stretching into the work routine benefits workers by improving physical health, mental well-being, and productivity. Encouraging regular stretching and providing opportunities for stretching breaks can create a healthier, more ergonomic work environment.Â